A rare case of spontaneous bladder perforation with osteomyelitis and paravesical abscess due to CA-MRSA clone USA100/ST5 - Torres da Silveira Ugino, Ricardo; Cassettari, Valéria; Ramos Martines, Brenda Margatho; Larenas, Ricardo Iturbe [UNESP]; Melocco, Gregory; Hidetoshi Fugita, Oscar Eduardo [UNESP] (Elsevier, 2022)
Spontaneous rupture of the urinary bladder represents a rare condition that may complicate with paravesical abscess. Although Staphylococcus aureus may be a part of the intestinal tract flora, it is an unusual cause of abdominal or pelvic abscesses. We report the case of a male patient with spontaneous bladder perforation with osteomyelitis and paravesical abscess, secondary to community-acquired methicillin-resistant Staphylococcus aureus infection.
Keywords: Bladder perforation; CA-MRSA; Osteomyelitis; Pelvic abscess; Penile prosthesis